Invited commentary: Differential learning is different from contextual interference learning - Schöllhorn, W. I. (Human Movement Science, 2016)
There has been renewed interest in the detailed structure of what is learned and the boundary conditions that foster motor learning. The accompanying article by Hossner et al. (2016), particularly their findings about augmented feedback in the context of different levels of additional noise, is consistent with this focus. Unfortunately, the findings from Hossner and colleagues appear to be based on incorrect interpretations of the differential learning (DL) approach. Essential discrepancies in the experimental conditions suggest the basis for the deviating results obtained in comparison to those of the original DL experiments. In this comment, it is also shown that the author`s assumptions and interpretations underlying CI and the DL approaches obscure crucial problems and contradictions of classical learning theory.